A vertebrate-conserved cis-regulatory module for targeted expression in the main hypothalamic regulatory region for the stress response - Gutiérrez Triana, José Arturo (BMC developmental biology, 2014)
Background: The homeodomain transcription factor orthopedia (Otp) is an evolutionarily conserved regulator of neuronal fates. In vertebrates, Otp is necessary for the proper development of different regions of the brain and is required in the diencephalon to specify several hypothalamic cell types, including the cells that control the stress response. To understand how this widely expressed transcription factor accomplishes hypothalamus-specific functions, we performed a comprehensive screening of otp cis-regulatory regions in zebrafish. - Results: Here, we report the identification of an evolutionarily conserved vertebrate enhancer module with activity in a restricted area of the forebrain, which includes the region of the hypothalamus that controls the stress response. This region includes neurosecretory cells producing Corticotropin-releasing hormone (Crh), Oxytocin (Oxt) and Arginine vasopressin (Avp), which are key components of the stress axis. Lastly, expression of the bacterial nitroreductase gene under this specific enhancer allowed pharmacological attenuation of the stress response in zebrafish larvae. - Conclusion: Vertebrates share many cellular and molecular components of the stress response and our work identified a striking conservation at the cis-regulatory level of a key hypothalamic developmental gene. In addition, this enhancer provides a useful tool to manipulate and visualize stress-regulatory hypothalamic cells in vivo with the long-term goal of understanding the ontogeny of the stress axis in vertebrates.
Gesehen am 07.07.2020